Smokin' seventeen : a Stephanie Plum novel - Evanovich, Janet (New York : Bantam Books, 2011)
Dead bodies are showing up in shallow graves on the empty construction lot of Vincent Plum Bail Bonds. No one is sure who the killer is, or why the victims have been offed, but what is clear is that Stephanies name is on the killers list.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; New Jersey -- Fiction; Mystery fiction